Impact of the COVID-19 Pandemic on the Incidence of Complicated Appendicitis in a Tertiary Medical Center, Amman, Jordan. A retrospective cohort. - Amarin, Marzouq; Al-Qawasmeh, Abdallah; Ghazzal, Hamza; AbuAnzeh, Rand; Kitaneh, Razi; Toubasi, Ahmad; Halaseh, Shahed (Jordan Medical Journal, 2024)
Abstract Objective: To assess the incidence of complicated appendicitis during the COVID-19 pandemic in Jordan University Hospital. Materials and Methods: in this cohort study, we retrospectively investigated data on acute appendicitis cases, two groups were established, the first group was the pandemic group, which includes patients who presented to the hospital during the period of acute restrictions and shutdowns extending from the 17th of March to the 6th of June 2020, and the pre-pandemic group which represents the same period in the previous year. These two groups were compared in terms of clinical characteristics and the prevalence of complicated appendicitis. Results: A total of 45 patients were included in the study, 24 in the pandemic group and 21 in the pre-pandemic group. Gender distribution was not significant between the two periods (P-value>0.05). Rates of occurrence of overall complications, preoperative complications, and intraoperative complications were similar indicating no significant difference between the two groups (P-value=0.526, 0.835, and 0.547, respectively). The duration between symptoms and admission and ALVARADO score were not significantly different between the two study groups. Also, the duration of in-hospital stay was numerically but not significantly lower in the 2019 (March-June) group compared to 2020 (March-June). Conclusion: In our study, there was no significant difference in the incidence of complicated appendicitis between pandemic and pre-pandemic groups.